Attitudes and Satisfaction of Burmese Learners Studying Thai Language in Language School of Thai Allied Committee with Desegregated Burma Foundation - Ngamnikorn, Tidarat (Thai Journal of East Asian Studies, 2012)
Background: The language school of Thai allied committee with desegregated Burma foundation, Ratchathewi district in Bangkok, had opened in order for teaching Burmese Thai language for ten years. There were many Bermese labors attending in class but many obstacles still occur. The educational efficiency and learning achievement in studying Thai language was not good as it should be. Therefore, a researcher was interested in studying about the attitude and satisfaction of Burmese learners for the purpose of taking the result of this research to be direction in educational development which was appropriate with students. It could be benefits for schools, students and be an example for other Thai language school teaching in this way. Objective: The purpose of this study was conducted with attitudes of Burmese learners studying Thai language in five aspects, for instance, the importance of learning Thai language, the subject, the method of teaching, teaching and learning activities, learning and teaching materials. Moreover, there are three aspects of satisfaction of Burmese learners studying Thai language such as the subject, learning and teaching activities, and teachers. The sample group was Burmese in language school of Thai Allied Committee with Desegregated Burmese Foundation, Rachatewee, Bangkok were selected the purposive sampling of 50 participants. Result: 1) Burmese learners had great attitudes toward learning Thai language. The greatest attitude was learning and teaching activities and the second was the importance of learning Thai language, the subject, learning and teaching material, and the method of teaching respectively. 2) Burmese learners had very high level in satisfaction toward learning Thai language. The highest satisfaction was teachers and the second was the subject and learning and teaching activities respectively. Discussion and conclusion: 1) The greatest attitude of Burmese Thai-language learners was teaching and learning activities especially listening skill for the purpose of practicing pronunciation and developing skill. Because listening was very important skill which lead to other skills such as speaking, reading, and writing. A second order was the importance of learning since it was used in work and relation between employer and employee. For subject matter, learners were good attitude in content which could be used in everyday life and communicate with Thai people. Moreover, in aspects of learning and teaching materials, learners were good viewpoint with books, textbooks, exercise books created by teachers which could make learners more understanding in education. The last one was method of teaching. Burmese learners were great attitude on teaching method which emphasized practicing 4 skills. It made learners known their level and could practice 4 skills effectively. 2) Satisfaction of Burnese Thai-language learners shown that the most satisfied was teacher because this foundation had a good teacher with good personality and human relations. The second was the subject which could be practiced 4 skills and apply to the real event. The last one was teaching and learning activities especially the activities focus on reading-writing and listening-speaking skills.